Upaya Tiongkok dalam Melindungi Intellectual Property pada Masa Pemerintahan Xi Jin Ping Periode 2008 – 2017 - Dhimas Pradipta Adi Guna; Ika Riswanti Putranti (International Relations, Faculty of Social and Political Sciences, Universitas Diponegoro, 2018)
This study discusses China's efforts in protecting intellectual property in a case study ofcooperation with the US during the reign of president Xi Jin Ping in 2008 - 2017. Thisstudy uses institutional liberal guidance that draws conclusions and theories from theempirical data collected in the field. The result of this research is that China's efforts inprotecting intellectual property have not been successful. China's joining the WTO andcooperation with the US have not been able to suppress the number of intellectual propertyviolations in China. The domestic legal system remains unclear, government oversight isinsufficient to make this case still continue to occur. China's inconsistent stance on anagreed treaty creates a new problem for the growing US-China relationship between thetwo countries. US lawsuits and allegations sent to the Chinese government for the theft oftechnology transfers prove that there is a desire of both countries to impose each other onbehalf of the national interest.